Rezidivierende E.-coli-Meningitis in der Neonatalperiode - Dierl, Alexander; Hanslik, Gregor (Monatsschrift Kinderheilkunde, 2023)
Background: Due to heterogeneous data, case studies with a small study population and different clinical constellations, a generally valid statement about the duration of antibacterial treatment in cases of neonatal meningitis is difficult. Single case reports could be helpful to optimize the antibacterial treatment strategy. Objective: This study illustrates our experience in the treatment of a female preterm infant with recurrent episodes of meningitis in the neonatal period after initial Escherichia coli sepsis. Possible risk factors and suggestions for improvement of the treatment strategy as well as different diagnostic options to exclude anatomical or immunological risk factors are demonstrated. Material and methods: Case report of a female preterm infant of 35 + 3 weeks gestational age with 3 episodes of E. coli meningitis. Results: In this case an administration period of 6 weeks was necessary for successful infection treatment. No anatomical aberrations or immunodeficiencies were present as risk factors for the three episodes of E. coli meningitis with sepsis. Using magnetic resonance imaging (MRI) and positron emission tomography computed tomography (PET-CT) as well as repeated imaging with ultrasonography, the diagnosis could also be presented in cross-sectional imaging. Conclusion: The optimal duration of treatment of neonatal meningitis still needs to be selected based on the patient-related risk factors as well as the results of the microbial examination. In our case, the causative pathogen (E. coli) was identified as a significant risk factor for recurrent meningitis and the need for prolonged antibacterial treatment.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Cerebrospinal fluid; Neonate; Pleocytosis; Preterm; Sepsis